Structure modification of luteolin and the influence of its derivatives on biological activities - Kong, Lingyang; Wu, Wei; Li, Chenliang; Ma, Lengleng; Ma, Junbai; Pan, Meitong; Jiang, Shan; Liu, Weili; Xu, Jiao; Ma, Wei (Frontiers in Nutrition, 2025)
IntroductionThis research aims to synthesize luteolin derivatives from hemp seeds by means of chemical synthesis, improve the synthesis process, simplify the procedure, and increase the yield to obtain new luteolin derivatives. Additionally, anti-inflammatory and antioxidant activities of hemp seed extracts and newly synthesized substances are tested to screen out substances with high anti-inflammatory and antioxidant activities.MethodsUsing luteolin as the raw material, acetyl, propionyl, and butyryl groups are introduced into the molecular structure of luteolin. A one-pot synthesis method is employed to modify the hydroxyl groups at positions 5, 7, 3′, and 4′ to obtain six new luteolin acyl derivatives. The molar ratio of reaction conditions is 1:4. Pyridine (20 mL) is used as the solvent, and the reaction is carried out at 25°C and 110°C. Exploring the anti-inflammatory and antioxidant activities of luteolin and its derivatives by establishing a psoriasis model.ResultsThe products are separated and purified by column chromatography and recrystallization, and six new luteolin acyl derivatives were synthesized: namely, 7,3′,4′-tri-O-acetylated luteolin (A), 7,3′,4′-tri-O-propionylated luteolin (B), 7,3′,4′-tri-O-butyrylated luteolin (C), 5,7,3′,4′-tetra-O-acetylated luteolin (D), 5,7,3′,4′-tetra-O-propionylated luteolin (E), and 5,7,3′,4′-tetra-O-butyrylated luteolin (F). By establishing a psoriasis like mouse model, the results showed that luteolin and its derivatives have good therapeutic effects on inflammation and antioxidation.DiscussionSix new acyl derivatives of luteolin were synthesized through structural modification, which improved their solubility and bioavailability. In the psoriasismodel, it has been proven that acyl derivatives of luteolin have anti-inflammatory and antioxidant activities, and have a relieving effect on psoriasis.Provide theoretical basis and potential treatment strategies for the future treatment of psoriasis.